In vitro Developmental Competence of Adult Sheep Oocytes Treated with Roscovitine - Crocomo, Letícia Ferrari; Ariu, F.; Bogliolo, L.; Bebbere, D.; Ledda, S.; Bicudo, S.D. [UNESP] (Wiley, 2016)
The efficiency of in vitro sheep embryo production is still low compared to that observed in vivo and in other species. In this context, meiotic inhibition strategies emerged as a promising alternative to improve this biotechnology. So, this study aimed to evaluate, for the first time, the effects of roscovitine on in vitro maturation of sheep oocytes and their subsequent embryo development. For this, cumulus-oocyte complexes (COCs) were cultured for 6 h in the presence (Rosco) or absence (Control) of 75 μm roscovitine and, subsequently, in vitro matured (IVM) for 18 h with gonadotropins. At 0 (Immature), 6 and 24 h of culture, the nuclear status of oocytes was evaluated by Hoechst staining. Embryo cleavage and blastocyst formation were recorded 30 h after in vitro fertilization and on day 7 of culture, respectively. Blastocyst quality was evaluated by differential staining. At 6 h, the GV rate in the Rosco treatment (93.8%) was similar to that observed in the Immature oocytes (94.9%) and significantly higher compared to Control (41.3%). After IVM for 18 h, a high and similar proportion of oocytes from Rosco (93.6%) and Control (88.4%) reached the MII stage. In both treatments, approximately 70% of oocytes cleaved and 50% of them developed up to blastocyst. The mean percentage of blastocyst cells, embryoblast, trophoblast and pyknosis did also not differ between Control and Rosco. In conclusion, roscovitine, at the studied experimental conditions, was efficient to reversibly inhibit the meiosis of adult sheep oocytes without detrimental effect on development and quality of the in vitro produced embryos.